Left Ventricular Dyssynchrony Parameters Measured by Phase Analysis of Post-stress and Resting Gated SPECT Myocardial Perfusion Imaging - Yanli Zhou; Dianfu Li; Jianlin Feng; Donglan Yuan; Zenic Patel; Kejiang Cao; Ji Chen (World Journal of Nuclear Medicine)
Phase analysis has been validated to measure left ventricular (LV) dyssynchrony from resting gated SPECT myocardial perfusion imaging (MPI). In 1-day rest/stress protocols, often only post-stress gated data are acquired. The purpose of this study was to determine whether LV dyssynchrony parameters measured at post-stress significantly differ from those measured at rest. Sixty normal subjects, 40 patients with stress-induced ischemia but normal LV function, and 29 patients with LV dysfunction were included in this study. All patients were scanned using a 2-day Technetium-99m sestamibi (MIBI) MPI protocol, where gated SPECT data were acquired at 60 min post injection of the radiotracer. LV dyssynchrony parameters at post-stress and at rest were calculated and compared using paired t-test. There were no significant differences in the LV dyssynchrony parameters between post-stress and resting in all cohorts. No patient showed differences in the LV dyssynchrony parameters between the post-stress and resting scans significantly greater than the reported variations in these parameters between serial resting scans. There was no significant difference in dyssynchrony parameters measured at rest and 60 min after stress on MPI gated images.